ANALISIS RASIO PROFITABILITAS UNTUK MENILAI KINERJA KEUANGAN PT WIJAYA CAHAYA TIMBER TBK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Joko; Sari, Cita Akhmalia; Purwantini, Heni (Perwira Journal of Economics & Business, 2025)
This research aims to determine the financial performance of PT. Wijaya Cahaya Timber Tbk in terms of profitability ratios for the period 2021 - 2022. The type of research used in this research is quantitative. Profitability ratios are used to see how much profit the company gets based on performance that affects financial statement records. There are several types of Profitability ratios that are used as measuring tools, namely Profit Margin on Sales, Return on Investment / ROI (Return on Investment), Return on Equity / ROE (Return on Equity for total asset turnover), Earning Per Share of Common Stock (Earnings Per Common Share). Based on the calculation results Profitability ratio at PT. Wijaya Cahaya Timber Tbk shows that there has been a decrease in all types of ratios from 2021 to 2022, the results achieved are still below industry standards which shows that the company's performance is still not good compared to other similar industries. In this case it is necessary to improve the company's operations in order to improve the company's performance and financial condition which is much better.